Impact of fibre and red/processed meat intake on treatment outcomes among patients with chronic inflammatory diseases initiating biological therapy: A prospective cohort study - Overgaard, Silja H.; Sørensen, Signe B.; Munk, Heidi L.; Nexøe, Anders B.; Glerup, Henning; Henriksen, Rikke H.; Guldmann, Tanja; Pedersen, Natalia; Saboori, Sanaz; Hvid, Lone; Dahlerup, Jens F.; Hvas, Christian L.; et al. (Frontiers in Nutrition, 2022)
Background Biologic disease-modifying drugs have revolutionised the treatment of a number of chronic inflammatory diseases (CID). However, up to 60% of the patients do not have a sufficient response to treatment, thus there is a need for optimization of treatment strategies. Objective To investigate if the treatment outcome of biological therapy is associated with the habitual dietary intake of fibre and red/processed meat in patients with a CID. Methods In this multicentre prospective cohort study, we consecutively enrolled 233 adult patients with a diagnosis of Crohn’s Disease, Ulcerative Colitis, Rheumatoid Arthritis (RA), Axial Spondyloarthritis, Psoriatic Arthritis and Psoriasis for whom biologic therapy was planned over a three year period. Patients with completed baseline food frequency questionnaires were stratified into a high fibre/low red and processed meat exposed group (HFLM; upper tertile) and an unexposed group (low fibre/high red and processed meat intake = LFHM). The primary outcome was the proportion of patients with a clinical response to biologic therapy after 14-16 weeks of treatment. Results Of the 193 patients included in our primary analysis, 114 (59%) had a clinical response to biologic therapy. In the HFLM group (N=64), 41 (64%) patients responded to treatment compared to 73 (56%) in the LFHM group (N=129), but the difference was not statistically significant (OR: 1.48, 0.72 to 3.05). For RA patients however, HFLM diet was associated with a more likely clinical response (82% vs. 35%; OR: 9.84, 1.35 to 71.56). Conclusion Habitual HFLM intake did not affect the clinical response to biological treatment across CIDs. However, HFLM diet in RA patients might be associated with better odds for responding to biological treatment, but this would need confirmation in a randomised trial. Trial registration clinicaltrials.gov/NCT03173144